PENGEMBANGAN BUKU AJAR KIMIA KOLOID MODEL PROBLEM BASED LEARNING GUNA MENGOPTIMALKAN HIGHER ORDER THINKING SKILL TERINTEGRASI GREEN CHEMISTRY - Encis Indah Suryaningsih (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This Research and Development type research aims to determine the characteristics, feasibility, effectiveness of the Colloidal Chemistry textbook model of Problem Based Learning (PBL) integrated with green chemistry, and the achievement of High Order Thinking Skills (HOTS) in a case study of Maritime University students. AMNI (UNIMAR AMNI) Semarang. The research method consists of define, design, and develop. The results of the study are: (1) textbooks have the following characteristics: the PBL model, integrated with green chemistry, contains HOTS indicators, is self-instructional, self-contained, stand-alone, adaptive, and user-friendly; (2) textbooks are suitable for use with a content feasibility score of 4.52, language 4.37, and presentation 4.65; (3) textbooks are used effectively, based on student learning outcomes in the knowledge aspect of 88.89%, the attitude and skill aspects show an increase and are in very good criteria; (4) Textbooks can optimize student HOTS, as evidenced by the N-Gain tests of students' critical and creative thinking skills of 0.85 and 0.90, the percentage of students' critical and creative thinking skills activities are 89% and 87%; and (5) the results of the student response questionnaire for small-scale and large-scale trials on positive criteria with percentages of 96.02% and 94.80%.